DOSIS PUPUK KOTORAN AYAM UNTUK MEMACU PERTUMBUHAN SEMAI MERANTI MERAH (Shorea leprosula Miq.) DI BAWAH NAUNGAN TEGAKAN KELAPA SAWIT - Lestari, Antisa Tria; Mardhiansyah, M.; Yoza, Defri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Shorea leprosula is one of the most important commercial timber in Southeast Asia. Nutrients are a source of nutrients or food needed by plants, one of which is by applying fertilizers. Chicken manure is an organic fertilizer that contains complete nutrients, both macro and micro. The aim of the research is to knowing influence and best dose of chicken manure fertilizer to seedling growth of Shorea leprosula in the shade of palm oil stands. The study used a completely randomized design (CRD) method consisting of 4 treatments and 4 replications so that 16 experimental units were obtained. The treatments were: (D0) 0% dose of chicken manure (control), (D1) 20% dose of chicken manure, (D2) 50% dose of chicken manure, (D3) 80% dose of chicken manure. Data were further analyzed using variance, with SPSS software version 20.0. If there is a significant effect of the treatment given, then the test (DNMRT) is carried out. Application of 20% chicken manure fertilizer is the best dosage treatment for chicken manure, namely (D1) by showing the increase in seedling height is 2.07 cm, and the plant dry weight is 1.59 g and top-root ratio is 2.38. Keywords : Chicken manure, Shorea leprosula Miq., growth, shade, oil palm stands.